2020
DOI: 10.1111/ina.12741
|View full text |Cite
|
Sign up to set email alerts
|

Loss of NO(g) to painted surfaces and its re‐emission with indoor illumination

Abstract: Heterogeneous surface reactions play a key role in the chemistry of the indoor environment because of the large indoor surface‐to‐volume ratio. The presence of photocatalytic material in indoor paints may allow photochemical reactions to occur at wavelengths of light that are present indoors. One such potential reaction is the heterogeneous photooxidation of NO to HONO. NO(g) is commonly found indoors, originating from combustion sources, ventilation and infiltration of outdoor air. We studied the interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The few published studies on indoor surface photochemistry indicate that surface photolysis could also contribute to the oxidative capacity indoors and influence indoor air composition, especially near surfaces such as painted walls 15,16,18,46,47 . However, surface photochemical reaction rates remain almost completely unquantified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few published studies on indoor surface photochemistry indicate that surface photolysis could also contribute to the oxidative capacity indoors and influence indoor air composition, especially near surfaces such as painted walls 15,16,18,46,47 . However, surface photochemical reaction rates remain almost completely unquantified.…”
Section: Discussionmentioning
confidence: 99%
“…Mixing ratios of HOCl, Cl capacity indoors and influence indoor air composition, especially near surfaces such as painted walls. 15,16,18,46,47 However, surface photochemical reaction rates remain almost completely unquantified. Photon fluxes at surfaces are one of the many uncertainties surrounding this chemistry.…”
Section: Effect Of Open Windows/doors On Indoor Photochemistrymentioning
confidence: 99%
“…8,11 Overall, NO x is partially responsible for urban smog, as well as acid rain and other pollution events harmful to human health. 12 Dirty city surfaces are known to be effective at recycling NO x ; 13,14 for example, Baergen and Donaldson 14 showed that heterogeneous photochemistry of nitrate anions present in the film of atmospheric constituents deposited onto urban surfaces (known as urban grime) produces NO x and other reactive species. Photochemical, humidity-dependent uptake of NO 2 onto urban grime has also been reported as a significant source of HONO, which could affect the oxidative capacity of the daytime urban atmosphere.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Atmospheric gases such as NO x (NO 2 and NO) are produced outdoors through the combustion of fossil fuels and are present in urban atmospheres at or up to several hundred parts per billion by volume. Reactions involving NO x and VOCs are responsible for the production of tropospheric ozone (O 3 ); furthermore, NO x is a precursor to HONO, which is a photochemical source of OH radicals under illumination conditions where O 3 chemistry is not important. , Overall, NO x is partially responsible for urban smog, as well as acid rain and other pollution events harmful to human health . Dirty city surfaces are known to be effective at recycling NO x ; , for example, Baergen and Donaldson showed that heterogeneous photochemistry of nitrate anions present in the film of atmospheric constituents deposited onto urban surfaces (known as urban grime) produces NO x and other reactive species. Photochemical, humidity-dependent uptake of NO 2 onto urban grime has also been reported as a significant source of HONO, which could affect the oxidative capacity of the daytime urban atmosphere. , In addition, NO x reacts heterogeneously with mineral dust, , a major component of road dust. , In this reaction, NO 2 first adsorbs to the surface of the dust, then produces gas-phase NO and nitrate. , Finally, road dust itself has recently been shown to be photochemically active; it can produce singlet oxygen upon illumination when in aqueous suspended state, which suggests the potential for heterogeneous photochemistry.…”
Section: Introductionmentioning
confidence: 99%